Computation of hypersonic re-entry flow - Lee, Choon Yee. (2013)
This project presents a computational study of hypersonic reentry flow over a blunt body. Fluent™ computational fluid dynamics software will be used to simulate the flow over a cylinder in 2 different conditions. The first set of simulations involves reentry flow at 65km at a Mach number of 22. The second set involves nitrogen gas flow at a speed of Mach number 6.14. The heat flux distribution over the cylinder is the main area of study in this project. The distributions are then compared to results validated by previous studies and research.